De novo ALK kinase domain mutations are uncommon in kinase inhibitor-naïve ALK rearranged lung cancers. (September 2016) - Lucena-Araujo, Antonio R.; Moran, Jason P.; VanderLaan, Paul A.; Dias-Santagata, Dora; Folch, Erik; Majid, Adnan; Kent, Michael S.; Gangadharan, Sidharta P.; Rangachari, Deepa; Huberman, Mark S.; Kobayashi, Susumu S.; Costa, Daniel B.
Highlights: ALK rearranged lung adenocarcinomas are responsive to crizotinib. However, ALK kinase mutations in crizotinib-naïve tumors have not been widely reported. ALK kinase mutations were uncommon (<3%) in ALK inhibitor-naïve lung adenocarcinomas. Abstract: Introduction: Anaplastic lymphoma kinase ( ALK ) rearranged lung adenocarcinomas are responsive to the multitargeted ALK inhibitor crizotinib. One of the common mechanisms of resistance to crizotinib is the acquisition of ALK kinase domain mutations. However, the presence of ALK mutations in crizotinib-naïve tumors has not been widely reported and it is unclear if de novo ALK mutations affect the response to crizotinib. Methods: We analyzed preclinical models of ALK rearranged lung cancers that were sensitive/resistant to ALK inhibitors, probed our institutional and other lung cancer databases for tumors with ALK kinase domain mutations, and evaluated tumor response to crizotinib. Results: ALK rearranged cell lines with ALK kinase domain mutations were heterogeneously less inhibited by increasing concentrations of crizotinib than cells driven solely by EML4-ALK fusions. Previous ALK rearranged lung cancer cohorts did not report ALK kinase mutations in inhibitor-naïve tumors. We identified one TKI-naïve ALK rearranged tumor with an ALK kinase domain mutation: ALK -S1206F (mutations at ALK-S1206 shifted crizotinib inhibitory curves only minimally in preclinical models). The never smoker whose tumor harbored de novo EML4 - ALK -E5;A20+ ALK -S1206F only achieved a 4-month radiographic response to crizotinib 250 mg twice daily. Conclusions: Combining data from our and prior cohorts, ALK kinase domain mutations were uncommon events (<3% of cases) in ALK inhibitor-naïve ALK rearranged lung adenocarcinomas but their effect on intrinsic resistance to ALK inhibitors should be better evaluated.